Craft Guilds as Synagogues: Further Thoughts on “Private Judean-Deity Associations” - Eckhardt, Benedikt (Journal for the study of Judaism, 2017)
The article responds to the challenge against the conventional understanding of ancient “synagogue” communities recently offered by Richard Last. While it is important to criticize the use of the term and some of its implications in modern scholarship, the argument that craft guilds worshipping the Judean deity among others should not be categorically distinguished from groups assembling only Ioudaioi and honoring only yhwh is shown to be based on a problematic understanding of several Greek inscriptions. It is precisely in the context of Graeco-Roman forms of social aggregation that this distinction is most pertinent.